Establishment and Characterization of Benzo(a)pyrene-Induced Skin Tumor in Rats - Sewoyo, Palagan Senopati; Adi, Anak Agung Ayu Mirah; Astawa, I Nyoman Mantik; Putra, I Gusti Agung Arta; Winaya, Ida Bagus Oka; Dayanti, Marissa Divia; Bramardipa, Anak Agung Bagus; Supartika, I Ketut Eli (Jurnal Veteriner; Vol 23 No 1 (2022), 2022)
Quite a number of research on cancer therapy strongly require an animal model of cancer. One of the chemicals commonly used to induce cancer in animal models is benzo(a)pyrene due to its carcinogenic effects. This study aims were to describe the gross pathology of the tumor-induced by benzo(a)pyrene in an olive oil solution (w/v), identify the type of tumor histopathologically, and finally, determine the correlation between the duration of the rats experiencing tumor and it’s grade score. Tumor grade score is important to assess in order to determine tumor malignancy. This study consisted of 10 white rats ( Rattus norvegicus ) were given two treatments: a negative control treatment (K-) was injected with 0.1 mL of olive oil and a positive control treatment (K+) was injected with 0.1 mL of 0.3 % (w/v) benzo(a)pyrene in olive oil solution. Each treatment rats was kept in a cage and monitored regularly. When the tumors macroscopically appeared in the interscapular area and were observed until reached 4 cm in size, the rats were then sacrificed and necropsied. Tumors were observed for the gross pathology to examine the shape and color of them, then routinely processed for histopathological evaluation. The results showed that the tumors’ cells appeared to be round (1/5), irregular (2/5), and multilobular (2/5). Based on histopathological observation, the types of tumors observed were classical fibrosarcoma (2/5) and pleomorphic fibrosarcoma (3/5). There is a significant association between the duration of the rats experiencing tumors and the tumor grade. The longer the rats have tumors, the tumors tend to be more aggressive.